EKSISTENSI HUKUM WARIS ADAT PADA SISTEM KEKERABATAN PATRILINEAL DI KABUPATEN SIKKA PROVINSI NUSA TENGGARA TIMUR - Agustina Dua Osa; Gisela Nuwa; Abdulah Muis Kasim (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2020)
The purpose of this research is to find out and explain the implementation of customary inheritance law and the process of inheritance dispute resolution based on the prevailing traditional inheritance law in Sikka Regency. This study used a qualitative approach to data collection using structured interviews, semi-structured, and observation. The sampling technique used in this study was snowball sampling. The data source used is primary data from interviews with 10 informants who are elders and administrators of village customary institutions in several villages in Sikka district. As for the results of the study, the situation describes the implementation of customary inheritance law in the patrilineal kinship system in Sikka Regency in that the distribution of land inheritance is given full power to the boys so that the distribution amount is different from the disabled children, while the dispute resolution process is based on negotiations after there is no resolution. deliberations to reconcile the disputing parties by the Village Traditional Institution and the Village Government. Keywords: Customary Inheritance Law, Patrilineal Kinship System, Sikka Regency.